Сколько истин я знал...: библиографический список литературы.: (к 50-летию со дня рождения В. В. Парамонова) / ЦГБ им. Фурманова (ЦГБ им. Фурманова, 1996)
Экземпляры: КР (20021210) / Инвентарный номер: у54868 / Цена: 1.00 / Сис.шифр: 91.9:83.3(2=Рус)6-8 / Авт.знак: С 44 / ГРНТИ: 17 / ББК: 91.9:83.3(2=Рус)6-8